RESPONS PERTUMBUHAN TANAMAN TOMAT (Solanum lycopersicum L) TERHADAP PEMBERIAN JAMUR Trichoderma sp - Nova Haryani; Syaiful Eddy; Dewi Novianti (Universitas PGRI Palembang, 2019)
ABSTRACTResearch Response of Tomato Plant Growth (Solanum lycopersicum L.) against the provision of Trichoderma sp Mushrooms, from April to June 2019 at the MIPA Faculty Workshop, University of Palembang PGRI, South Sumatra. This study aims to determine. The growth Response of Tomato Plants to the administration of Trichoderma sp. This research method uses a completely randomized design with 6 treatments and 4 replications, namely P0 (without Trichoderma sp pellets), P1 (20 grams of Trichoderma sp pellets/kg soil), P2 (40 grams of Trichoderma sp pellets/kg soil), P3 (60 grams of Trichoderma sp pellets/kg soil), P4 (80 grams of Trichoderma sp pellets/kg soil), P5 (100 grams of Trichoderma sp pellets/kg soil), analyzed by ANSIRA at the level of 5%. The parameters observed in this study were plant height, stem diameter and number of leaves. Sidik Ragam Analysis result that the administration of Trichoderma sp significantly affected plant height, stem 80 grams of Trichoderma sp pellets/kg soil with an average plant height of 15,75 cm, stem diameter of 1,2 mm, and number of leaves of 18,75 strands, while the lowest yield was in a flat treatment without Trichoderma sp plant height 3 cm, stem diameter 0,1 mm, and number of leaves 4 strands. Keywords: Trichoderma sp, growth, tomatoes (Solanum lycopersicum) ABSTRAKPenelitian Respons Pertumbuhan Tanaman Tomat (Solanum lycopersicum L.)Terhadap Pemberian Jamur Trichoderma sp, pada bulan April sampai dengan bulan Juni 2019 di Workshop Fakultas MIPA Universitas PGRI Palembang, Sumatera Selatan. Penelitian ini bertujuan untuk mengetahui respons pertumbuhan tanaman tomat terhadap pemberian jamur Trichoderma sp. Metode penelitian ini menggunakan Rancangan Acak Lengkap dengan 6 perlakuan dan 4 ulangan yaitu P0 (tanpa pelet Trichoderma sp), P1 (20 gram pelet Trichoderma sp/kg tanah), P2 (40 gram pelet Trichoderma sp/kg tanah), P3 (60 gram pelet Trichoderma sp/kg tanah), P4 (80 gram pelet Trichoderma sp/kg tanah), P5 (100 gram pelet Trichoderma sp/kg tanah), dianalisis dengan ANSIRA pada taraf 5%. Parameter yang diamati dalam penelitian ini adalah tinggi tanaman, diameter batang dan jumlah daun.Hasil Analisis Sidik Ragam bahwa pemberian Trichoderma sp berpengaruh nyata terhadap tinggi tanaman, diameter batang, dan jumlah daun. Perlakuan terbaik terdapat pada perlakuan 80 gram pelet Trichoderma sp/kg tanah dengan rata-rata tinggi tanaman 15,75 cm, diameter batang 1,2 mm, dan jumlah daun 18,75 helai, sedangkan hasil terendah pada perlakuan tanpa pelet Trichoderma sp dengan rata-rata tinggi tanaman 3 cm, diameter batang 0,1 mm, dan jumlah daun 4 helai. Kata Kunci: Trichoderma sp, pertumbuhan, tomat (Solanum lycopersicum L.)